AKAD WAKALAH DANA SETORAN HAJI PERSPEKTIF HUKUM ISLAM - Ali Minanto (Jurnal AL-AHKAM, 2023)
This study aims to look at the law on wakalah contracts for haj deposit funds. This research uses library research. Data collection was carried out by accessing various sites from the internet (websites) and the data sources used were secondary data sources. The development of such a large haj fund has the potential to be used to support a higher quality haj pilgrimage. Hajj financial management that is effective, efficient, transparent, accountable and in accordance with statutory provisions will have a positive impact on Indonesian pilgrims. Efforts made by the Ministry of Religion to improve the quality of organizing the pilgrimage is to develop these funds through investment. The formulation of the problem is the wakalah contract for haj deposit funds from the perspective of Islamic law. The questions that arise are the pros and cons of haj funds investing in haj deposits, the view of maslahah mursalah, and the wakalah contract of haj funds from the perspective of Islamic law. Wakalah in the pilgrimage fund is permissible as long as it aims to help fellow human beings. Maslahah The management of funds in infrastructure makes it easier for Indonesian hajj pilgrims